Transmembrane Protein 100 Inhibits the Progression of Colorectal Cancer by Promoting the Ubiquitin/Proteasome Degradation of HIF-1α - Zheng, Ying; Zhao, Yitong; Jiang, Jiong; Zou, Baicang; Dong, Lei (Frontiers in Oncology, 2022)
Transmembrane protein 100 (TMEM100) is involved in embryonic cardiovascular system development. However, the biological role of TMEM100 in human cancers, particularly colorectal cancer (CRC), is unclear. In this study, tissue microarrays were stained using immunohistochemistry methods to evaluate the association between TMEM100 levels and clinic-pathological features for CRC. Kaplan–Meier and log-rank tests revealed that decreased levels of TMEM100 correlated with shorter overall survival. Cox regression revealed that reduced levels of TMEM100 was an independent prognostic factor for detrimental survival in CRC. A lentiviral vector was used to overexpress TMEM100 in HCT116 cells, and small interfering RNA was used to knockdown TMEM100 in SW480 cells. The CCK-8 assay, colony formation analysis, cell cycle analysis, cell migration assay, mouse xenograft model and mouse lung metastasis model showed that TMEM100 suppressed CRC cell proliferation and migration in vitro and in vivo. IHC scores of TMEM100 and HIF-1α were significantly negatively correlated. A half-time determination analysis in which cells were treated with cycloheximide revealed that TMEM100 shortened the HIF-1α half-life. Further immunoprecipitation experimental results showed that TMEM100 promoted the ubiquitination of HIF-1α, which caused HIF-1α degradation via the 26S proteasome pathway. Angiogenesis assay and migration assay results revealed that TMEM100 suppressed the migration and angiogenesis induction capacities of HCT116 cells, but this inhibitory effect was abolished when HIF-1α degradation was blocked by MG132 treatment. These results indicated that TMEM100 inhibited the migration and the angiogenesis induction capacities of CRC cells by enhancing HIF-1α degradation via ubiquitination/proteasome pathway.